Puntos de Encuentro: Exercising Active Forms of Citizenship in Buenaventura, Colombia - Carlos Alberto Valderrama Renteria; Sandra Patricia Palacios Moreno (Latin American Research Review)
The present article focuses on a place-based repertoire of contention known as Punto de Encuentro, designed to defend a rural-urban territory against racialized processes of economic globalization and armed conflicts in Colombia. The article suggests that citizenship becomes meaningful when Afro-Colombians exercise their rights to their territories. To support this argument, the article delves into the 2017 civic strike mobilizations that reclaimed the city space of Buenaventura as a territory of life where Afro-Colombians can live with dignity and in peace. As the article describes, the civic strike activists created four crucial social participation processes: the crafting of a social movement, the production of a place-based knowledge from past struggles, the construction of a common ethical and political framework, and Puntos de Encuentro as places of social and cultural resistance.